Clinical characteristics of medium and large T1-T4 choroidal melanomas in Ukraine (Ukrainian Journal of Ophthalmology, 2025)
Purpose. To evaluate the clinical characteristics of medium to large Т1-Т4 choroidal melanomas (CM) in patients treated at SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine”.Material and Methods. We retrospectively reviewed the medical records of 283 patients treated for medium to large CM at SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the NAMS of Ukraine” in 2007-2024. The study sample consisted of 125 men (44.2%) and 158 women (55.8%), with a mean age (standard deviation (SD)) of 54.2 (12.4) years. Patients underwent standard ophthalmological examination. Additionally, they received ocular ultrasonography using a Cinescan ultrasound system, OCT examination using a Stratus OCT 300 system and fluorescein angiography. No metastasis was detected in any patient at presentation and the start of treatment.Results. The case distribution included stage T1 in 15 patients (5.3%), stage T2 in 132 patients (46.64%), stage T3 in 115 patients (40.64%), and stage T4 in 21 patients (7.42%). Paramacular and peripheral locations of CM were more common in the total sample (88.4%) (p
Keywords: ophthalmic oncology,; choroidal melanoma,; tumor stage; retina; choroid; transpupillary therapy; ionizing radiation